1986
DOI: 10.1111/j.1365-2125.1986.tb02827.x
|View full text |Cite
|
Sign up to set email alerts
|

Debrisoquine oxidation in an Australian population.

Abstract: 1 The standard laboratory method for determination of debrisoquine phenotype has been modified and shortened with no loss of sensitivity. Debrisoquine metabolic ratios (MR) at 4 and 8 h showed excellent correlation indicating that collection time can also be shortened. Same day phenotyping is therefore possible. 2 One hundred normal, Caucasian Australian subjects were phenotyped (46 males, 54 females) and 6% were poor metabolisers (PM) of debrisoquine. 3 Fifty of the original subjects were also acetylation phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…In a large Swedish study the incidence of poor hydroxylators of mephenytoin was 2.8%; debrisoquine was 8.9% (5). This is similar to data previously reported (7)(8)(9)(10)(11)(12)(13) and our own study. To maximize the detection of differences in hydroxylation capacity migraineurs were not allowed to take drugs known to be metabolized by the probes (14)(15)(16)(17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 91%
“…In a large Swedish study the incidence of poor hydroxylators of mephenytoin was 2.8%; debrisoquine was 8.9% (5). This is similar to data previously reported (7)(8)(9)(10)(11)(12)(13) and our own study. To maximize the detection of differences in hydroxylation capacity migraineurs were not allowed to take drugs known to be metabolized by the probes (14)(15)(16)(17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 91%
“…About 5 to 10% of the Caucasian population (Brosen et al 1985;Dick et al 1982;Eichelbaum et al 1979;Evans et al 1980;Peart et al 1986;Schmid et al 1985;Steiner et al 1985;Syvalahti et al 1986;Wedlund et al 1984) and about 0 to 0.7% of the Japanese and Chinese have an impaired ability to eliminate debrisoquine and are termed poor metabolisers (Horai et al 1989;Luo et al 1987;Nakamura et al 1985). The polymorphic ability to oxidise debrisoquine is a major factor in determining the pharmacological and toxicological effects of many drugs, including {3-blockers.…”
Section: Consequences Of Debrisoquine Polymorphism On the Dispositionmentioning
confidence: 97%
“…The results of this theoretical study together with experimental data for debrisoquine (Steiner et al 1985) indicate that heterozygotes can only be identified unequivocally by pedigree analysis. Jackson et al (1986) also predicted that the time of urine collection would make very little difference to the shape and position of the frequency distribution, a finding which has been verified experimentally for debrisoquine (Peart et al 1986).…”
Section: Theoretical Aspectsmentioning
confidence: 78%